2014
DOI: 10.1364/ol.39.003888
|View full text |Cite
|
Sign up to set email alerts
|

Resolution analysis in computational imaging with patterned illumination and bucket detection

Abstract: In computational imaging by pattern projection, a sequence of microstructured light patterns codified onto a programmable spatial light modulator is used to sample an object. The patterns are used as generalized measurement modes where the object information is expressed. In this Letter, we show that the resolution of the recovered image is only limited by the numerical aperture of the projecting optics regardless of the quality of the collection optics. We provide proof-of-principle experiments where the sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…To boost up the image acquisition, we take advantage of the ground-breaking theory of compressive sensing (CS), which makes it possible to recover an N -pixels image from M < N measurements [24,25]. In CS, one takes 145 samples of the N-dimensional transmission vector T using a matrix M × N matrix S , obtaining undersampled measurements Y = S T. Along this section, and with no lack of generality, we will refer to the transmission signal, where an identical relation holds for the reflection mode.…”
Section: Compressive Sensing Retrievalmentioning
confidence: 99%
See 2 more Smart Citations
“…To boost up the image acquisition, we take advantage of the ground-breaking theory of compressive sensing (CS), which makes it possible to recover an N -pixels image from M < N measurements [24,25]. In CS, one takes 145 samples of the N-dimensional transmission vector T using a matrix M × N matrix S , obtaining undersampled measurements Y = S T. Along this section, and with no lack of generality, we will refer to the transmission signal, where an identical relation holds for the reflection mode.…”
Section: Compressive Sensing Retrievalmentioning
confidence: 99%
“…Other structured illumination approaches have also been implemented for microscopy during the past few years. The single-pixel imaging (SPI) scheme [13] has gained considerable attention as a very effective sensing mechanism and has triggered diverse applications where conventional cameras equipped with 25 millions of pixels fail to give an adequate response, including optical microscopy [14]. As a matter of fact, SPI allows imaging at previously undeveloped spectral bands [15,16], at the photon-counting regime [17], in presence of strong turbulence or scattering [18,19], and also through multimode optical fibers [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 Combining patterned illumination with the single-pixel detection strategy, it has been shown that the resolution of the reconstructed image is limited only by the NA of the projecting optics, regardless of the quality of the collection optics. 63 An apodization filter without adjustable parameters based on the application of the Lukosz bound was proposed to achieve the artifact-free reconstruction. 64 With 3D SIM, an additional 2-fold increase in the axial resolution can be achieved by modulating the excitation light along the z -axis using 3-beam interference and processing a z -stack of images accordingly.…”
Section: Available Super-resolution Microscopy Techniquesmentioning
confidence: 99%
“…The reference arm has been removed in computational ghost imaging (CGI) and replaced with sequential illumination patterns generated by a spatial light modulator (SLM) [6][7][8]. The patterned illumination and bucket detection in CGI significantly improve the performance of photon counting imaging [9], scattering imaging [10] and Terahertz imaging [11].…”
Section: Introductionmentioning
confidence: 99%